2016
DOI: 10.1186/s13293-016-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in fetal and infant growth patterns: a prospective population-based cohort study

Abstract: BackgroundThe objective of this study was to assess whether sex-specific differences in fetal and infant growth exist.MethodsThis study was embedded in the Generation R Study, a population-based prospective birth cohort. In total, 8556 live singleton births were included. Fetal growth was assessed by ultrasound. During the first trimester, crown-rump-length (CRL) was measured. In the second and third trimester of pregnancy head circumference (HC), abdominal circumference (AC) and femur length (FL) were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 35 publications
8
67
2
Order By: Relevance
“…We hypothesized that the sex‐specific differences in growth promoting effects of the foetal growth factors contribute to the different growth strategies of males and females, resulting in sex differences in birthweight and length at birth. Such differences have been shown in earlier studies …”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…We hypothesized that the sex‐specific differences in growth promoting effects of the foetal growth factors contribute to the different growth strategies of males and females, resulting in sex differences in birthweight and length at birth. Such differences have been shown in earlier studies …”
Section: Introductionsupporting
confidence: 85%
“…22,23 In our study, we found consistent significant positive associations of IGF2 with growth outcomes in males, and similar associations in females, although only significant for birthweight. IGF2 expression levels in placental tissue measured early in pregnancy (at weeks [11][12][13] are associated with birthweight, especially with small for gestational age neonates. 24 Associations between IGF2 and growth outcomes continue to exist at least until the age of 5 years, 25 The positive associations of cord blood IGF-1 and C-peptide with birthweight, length and placenta weight found here is in line with literature in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that there were no differences in GA between PE and control groups (Table ). However, the combination of BPD, head circumference, abdominal circumference, and FL provides a better estimation of GA than CRL during 2nd and 3rd trimesters of gestation …”
Section: Discussionmentioning
confidence: 99%
“…The studied infants included 709 girls and 767 boys born between weeks 25 and 39 of gestation. Due to the dimorphic differences that are already present from the first trimester of pregnancy onwards and continue throughout pregnancy, calculations have been performed separately for girls and for boys.…”
Section: Methodsmentioning
confidence: 99%